Efeito do anabolizante decanoato de nandrolona na expressão de marcadores miogênicos e no processo de reparo muscular após criolesão - Piovesan, Roberto Farina (2010)
The objective of this study was to analyze the effect of the anabolic steroid nandrolone decanoate on muscle repair and expression of myogenic markers after cryolesion in rat skeletal muscle. We studied 100 male Wistar rats were divided into four groups: (1) Control (n = 10), (2) sham control (n = 10) only underwent incision and exposure of the anterior tibial muscle (3) and cryolesioned treated with anabolic and sacrificed after 1, 7, 14 and 21 days (n = 40), (4) cryolesioned and treated with vehicle and sacrificed after 1, 7, 14 and 21 days (n = 40). Treatment with steroid injections consisted of Nandrolone decanoate intramuscular 5mg/kg twice a week. The animals were sacrificed and the TA was removed for total RNA extraction for analysis of MyoD and myogenin by real time PCR and morphological analysis of the repair process using hematoxylin-eosin. The results showed a significant increase in MyoD mRNA in group cryolesioned 7 days and treated with steroid compared to its respective group without cryolesion and treated with steroid and vehicle groups with or without injury, this same period. With respect to myogenin, 21 days after it was verified a significant increase in expression in the injury group treated with steroid compared to other groups of that period. The morphological analysis showed that after 7 days there was no edema and myonecrosis and 14 days in the absence of edema and inflammatory infiltrate only in the injury group treated with steroid compared to other groups of the same period. In conclusion, the anabolic steroid nandrolone decanoate accelerates tissue repair in rats after cryolesion and induces a significant increase in MyoD after 7 days and myogenin after 21 days of injury.